The Role of Employee Job Satisfaction: Work Discipline and Work Environment - Muhammad Taufik Lesmana; Asrizal Efendy Nasution; Dedi Tri Handoko (Journal of International Conference Proceedings (JICP), 2022)
This study was conducted to determine and analyze the effect of work discipline and work environment on employee job satisfaction at PT. Perkebunan Nusantara III (Persero) Medan. The population in this study were all employees of PT. Perkebunan Nusantara III (Persero) Medan in the Human Resources (HR) section, totaling 44 people. Sampling using a saturated sample that is using the entire existing population as a sample. Data collection techniques using questionnaires and interviews. The data analysis technique used multiple linear regression, hypothesis testing, and coefficient of determination. The results of this study indicate that work discipline has no significant effect on employee job satisfaction, while the work environment has a significant effect on employee job satisfaction. Simultaneously, this study proves that work discipline and work environment have a significant effect on employee job satisfaction at PT. Perkebunan Nusantara III (Persero) Medan. Keywords: Work Discipline, Work Environment, Job Satisfaction